Imperfect Competition and the Design of VAT Regimes : The Case of Energy Trade Between Russia and Ukraine - Shiells, Clinton (IMF Working Papers; Working Paper, 2002)
Under imperfect competition, Russia and Ukraine may choose to deviate from optimal tax considerations which suggest use of a destination-based VAT regime. Oil and gas trade is a major source of Russian tax revenue, which is collected partly through an origin-based VAT on intra-CIS energy trade. The paper shows that Ukraine may try to capture part of the tax revenue if it has monopsony power. It is far from clear whether Ukraine would succeed in shifting the rents through taxation, since this depends on the form of imperfect competition and the curvature of Ukraine's import demand function.